2020
DOI: 10.1016/j.jaip.2020.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Asthma Health Care Utilization, Viral Testing, and Air Pollution Changes During the COVID-19 Pandemic

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic caused dramatic changes in daily routines and health care utilization and delivery patterns in the United States. Understanding the influence of these changes and associated public health interventions on asthma care is important to determine effects on patient outcomes and identify measures that will ensure optimal future health care delivery. Objective We sought to identify changes in pediatric asthma-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
139
4
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(175 citation statements)
references
References 41 publications
19
139
4
4
Order By: Relevance
“…The reduction of respiratory pathology admission such as asthma is related to changes in respiratory virus infections (ie reduction of the contribution of person-to-person transmission of respiratory viruses) and also to less exposure to inhalant allergens related to facial mask and lockdown [ 26 , 27 ]. In addition to potentially changing levels of outdoor air pollutants, COVID-19 related public health interventions likely influenced pollution exposure profiles of children in other ways, including via decreased commuting and outdoor activity [ 27 ]. Another mechanism to reduce allergic responses include include the physical filtration of face masks and the potentially modified physiological response to allergens by breathing humid and hot air [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of respiratory pathology admission such as asthma is related to changes in respiratory virus infections (ie reduction of the contribution of person-to-person transmission of respiratory viruses) and also to less exposure to inhalant allergens related to facial mask and lockdown [ 26 , 27 ]. In addition to potentially changing levels of outdoor air pollutants, COVID-19 related public health interventions likely influenced pollution exposure profiles of children in other ways, including via decreased commuting and outdoor activity [ 27 ]. Another mechanism to reduce allergic responses include include the physical filtration of face masks and the potentially modified physiological response to allergens by breathing humid and hot air [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the Japanese government convinced businessmen to stay and work at home during the ‘voluntary lockdown’ starting in April 8 . Previous reports have shown that adherence improved during lockdown for the COVID-19 pandemic 9 . Besides, PM2.5 was one of the environmental risk factors that decreased in several areas, including India, China, England, and The United States during lockdown.…”
Section: Discussionmentioning
confidence: 86%
“…During the pandemic, children with asthma experienced improved disease control (two thirds of the patients), as evidenced by improved scores in validated asthma control measures (>MCID in one third), fewer asthma attacks, fewer hospitalizations, and improved pulmonary function. The multifaceted etiology of this observation may include the avoidance of major asthma triggers including outdoor allergens, viral infections, physical exercise and air pollution, due to social distancing, home sheltering and reduced school days 10,12,22,23,24,25 . Increased treatment adherence during the pandemic 26 , could have also contributed and is consistent with the high adherence levels observed during the pandemic in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is also possible that allergic sensitization can have some protective effect against COVID-19 11 . However, this needs to be further explored 12,13 .…”
Section: Introductionmentioning
confidence: 99%